(untitled) (Research, Society and Development, 2022)
Dexmedetomidine uses widely in veterinary medicine. This drug achieves analgesic, sedative, and muscular relaxation, and can be administered intravenously in continuous infusion with or without an initial bolus. But cardiovascular and respiratory alterations had been considered. This review aimed to analyze the effect of cardiovascular and respiratory in dogs under continuous infusion of dexmedetomidine. For the selection of studies, words like dogs, dexmedetomidine, and continuous infusion, were inserted into the Pubmed and Embase platforms. And 11 studies were admitted, with pre-established inclusion and exclusion criteria, to perform the meta-analysis. The articles used dexmedetomidine at doses ranging from 0.1-4.5 µg/kg and different associations. The reduction of general anesthetics with dexmedetomidine alone was 11% to 69%. And when associated with another drug can reduce the general anesthetic by 86%. In the cardiovascular system, dexmedetomidine increased mean arterial pressure and decreased heart rate in a dose-dependent (P < 0.00). There was also a decrease in cardiac output and index (P < 0.00). In respect of respiratory parameters, there were no significant differences in respiratory rate, carbon dioxide, and oxygen in arterial blood. In conclusion, dexmedetomidine decreases the consumption of general anesthetics. Increases mean arterial pressure while reducing heart rate, output, and cardiac index in a dose-dependent manner without significantly altering respiratory function.